‘YAMPIL INSPIRATIONS’: A STUDY OF THE DNIESTER CULTURAL CONTACT AREA AT THE FRONTIER OF PONTIC AND BALTIC DRAINAGE BASINS - Ivanova, Svetlana; Klochko, Viktor; Kośko, Aleksander; Szmyt, Marzena; Toschev, Gennadiy; Włodarczak, Piotr (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni., 2015)
The article presents the present state of research on the general issue of the dniester region of cultural contacts between communities settling the Baltic and Pontic drainage basins . Some five domains of research shall be brought to discussion in which it is possible to see fresh opportunities for archaeological study, on the basis of ‘Yampil studies’ on dniester-Podolia (forest-steppe) barrow-culture ceremonial centres from the latter half of the 4th millennium and first half of the 3rd millennium BC . This relates to the peoples of the Eneolithic and the Early Bronze age . in terms of topogenesis, embracing the Pontic-Tripolye, Yamnaya and Catacomb cultures, as well as Globular amphora and Corded ware in central prehistoric Europe .
Keywords: barrow cultures; Tripolye; Yamnaya; Catacomb; Globular Amphora; Corded Ware; Middle Dniester Area